การตรวจสอบคุณภาพของนํ้าดื่มบรรจุขวดที่จำหน่ายในจังหวัดฉะเชิงเทรา Monitoring Qualities of Bottled Drinking Water Sold in Chachoengsao Province - นิ่มรัตน์ สุบัณฑิต นิ่มรัตน์; วุฒิพันธุ์ชัย วีรพงศ์ วุฒิพันธุ์ชัย (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ ในการศึกษาครั้งนี้ไดท้ ำการศึกษาถึงคุณภาพทางจุลชีววิทยา คา่ ความเปน็ กรด - ดา่ ง และลักษณะที่ปรากฎ ของนํ้าดื่มบรรจุขวดที่จำหน่ายในจังหวัดฉะเชิงเทรา ประเทศไทย พบว่าตัวอย่างนํ้าดื่มบรรจุขวดจำนวน 33 ตัวอยา่ ง ที่บรรจุในขวดพลาสติกใสและพลาสติกขุน่ มีปริมาณแบคทีเรียกลุม่ โคลิฟอรม์ และฟคี ัลโคลิฟอรม์ น้อยกว่า 2.2 MPN ต่อมิลลิลิตร และไม่พบ Escherichia coli ในทุกตัวอย่าง ส่วนค่าความเป็นกรด - ด่าง ของนํ้าดื่มพบว่า ร้อยละ 36.36 มีค่าความเป็นกรด - ด่างน้อยกว่า 6.5 แต่ทุกตัวอย่างที่ตรวจมีลักษณะใส และไมมี่กลิ่น ดังนั้นน้ำดื่มที่นำมาตรวจนี้ผา่ นเกณฑต์ ามมาตรฐานน้ำดื่มในภาชนะบรรจุที่ปดิ สนิทที่กำหนด โดยกระทรวงสาธารณสุขของประเทศไทย ด้านจุลชีววิทยาร้อยละ 100 แต่ผ่านเกณฑ์มาตรฐานด้านเคมี (ค่าความเป็นกรด - ด่าง) ร้อยละ 63.64 เท่านั้น Abstract In this study, the microbiology, pH and some qualities of bottled drinking water distributed in Chachoengsao Province, Thailand were examined. The results showed that 33 samples of both clear and opaque bottled drinking water in terms of coliform bacteria and fecal coliform bacteria in water samples were less than 2.2 MPN/100 mL. Escherichia coli was not found in any samples. pH values of 36.36% samples were less than 6.5, but all tested samples were clear and odourless. Therefore, both types of bottled drinking water samples met the standard based on the standard for drinking water in sealed container set by Ministry of Public Health of Thailand, in terms of microbiological standard for 100% and chemical standard (pH quality) for 63.64%.